Pre and Post Merger Financial Performance of Merged Banks in India - A Select Study - Srinivas, K. (Indian Journal of Finance, 2010)
The 1990s saw partial liberalization of the banking industry and the emergence of new private sector banks as well as international banks. During the next few years, fears of liberalization were put to rest and in the past decade, the banking system has gained much from it. Liberalization brought out the best in the industry; inducing competitive spirit among various banks. Also, during this period, the banks put in place effective risk management mechanisms and added fresh capital, which is very important to the banking industry. By concentrating on the top-line and bottom-line, banks across the board have improved their profit while reducing their operational costs and more number of banks have improved their financial performance by using the concept of mergers and acquisitions.